2016
DOI: 10.3174/ajnr.a4839
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Observation of Brain Injury by MRI and Malignant Electroencephalography Patterns in Comatose Survivors of Cardiac Arrest following Therapeutic Hypothermia

Abstract: Background and Purpose Malignant EEG patterns are considered predictive of poor outcome in comatose survivors of cardiac arrest. We hypothesize that malignant patterns by EEG are associated with evidence of more severe brain injury on MRI. Materials and Methods Retrospective review of clinical, imaging and EEG data of 33 adult comatose survivors of cardiac arrest following therapeutic hypothermia was performed. Outcomes measured included discharge destination and survival. Imaging studies were visually score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…As already mentioned by the authors of this study, one can postulate that this finding is explained by the extensive structural brain damages impeding the generation of detectable epileptiform activity. This also corroborates the conclusions of the study from Mettenburg et al, 15 who reported that EEG patterns defined by the presence of epileptiform activity were associated with less severe brain injury in the MRI.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As already mentioned by the authors of this study, one can postulate that this finding is explained by the extensive structural brain damages impeding the generation of detectable epileptiform activity. This also corroborates the conclusions of the study from Mettenburg et al, 15 who reported that EEG patterns defined by the presence of epileptiform activity were associated with less severe brain injury in the MRI.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, there is no consensus about the way to characterize patterns in diffusion restriction for outcome prognostication after CA. Among different approaches, the whole-brain averaged ADC value, 15,27 the percentage of brain volume below a certain threshold, 10 or the topography of regions with reduced ADC 30 have been used. Since automated methods with voxel-wise ADC measurements are not yet widely available for clinical use, 30 we decided to use an anatomical based classification.…”
Section: Mri Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a recent study showed that epileptiform EEG patterns do not consistently reflect diffuse cortical injury assessed by cerebral MRI. 23 In the present series, we observed a remarkable efficacy of perampanel oral loading (6-12 mg) in terminating superrefractory NCSE in postanoxic patients within 72 hours of administration. In all cases, perampanel was added to the antiepileptic and anesthetic drug regimen already in use.…”
Section: Discussionsupporting
confidence: 49%
“…We have recently demonstrated heterogeneity in MRI findings between those with malignant and non-malignant cEEG patterns. 34 These data suggest that patients with diffuse cerebral edema may lack the neuronal substrate necessary to generate malignant EEG patterns. Severe edema is more likely to result in profound suppression of EEG.…”
Section: Discussionmentioning
confidence: 95%